A theoretical model of cognitive factors that affect auditors' performance and perceived independence. (1st February 2010) - Kleinman, Gary; Anandarajan, Asokan; Medinets, Ann; Palmon, Dan
Auditor independence is a guiding principle of the relationship between auditors and clients, and a key component of outsiders' acceptance of firms' financial statements. As recent accounting scandals have illustrated, the audit process is meaningless without the auditor's impartial judgement. While Kleinman, Palmon and various colleagues (1998, 2000a, 2001 and 2003) have developed a framework based on the behavioural science literatures to understand the auditor-client relationship, this framework excludes the effects of expertise, cognitive heuristics and affect on the outcomes of situations that might challenge auditor independence. This paper draws on the Mayer (2003) and Libby and Luft (1993) models and other literature to develop a cognitive model of factors that may affect perceived independence and auditor's performance. This model should help interested parties better understand situations that may impair the perceived independence of auditors. Suggestions for improving the auditor's reasoning process are presented, as are research suggestions.